"GLOBAL BRITAIN" IN INTERNATIONAL POLITICS AND STRATEGIC OPTIONS OF SERBIA IN RELATIONS WITH THE UNITED KINGDOM - Krstic, Milan (Serbian political thought, 2023)
British influence on the Balkans has been present since early 19th century, this geopolitical change got the attention of the Western Balkan relations analysts as well. This text aims to provide an answer to the question of what kind of United Kingdom’s policy can be expected towards the Western Balkans region, and towards the Republic of Serbia in particular, as well as what strategic options Serbia has at its disposal in its relationship with official London. The paper claims that the United Kingdom's actions in the region will be largely determined by the global British strategy, aimed primarily at preventing the spread of Russian and, to a lesser extent, Chinese global influence. It is also claimed that Serbia's attitude towards Russia and, to a lesser extent, China will primarily affect the future of Belgrade-London relations, although other issues will certainly have an impact (Kosovo and Metohija, Bosnia and Herzegovina, security cooperation with NATO, etc.). Through analysis of main strategic documents in the field of foreign and defence policy, as well as through the analysis of the recent UK behavior in international relations, the first part of the paper presents the international strategy of "Global Britain" after Brexit and outlines the general international goals of the UK.  The second part of the paper presents British in the Western Balkans region. The third part of the paper presents a brief overview of Serbian-British relations in the last five years and points to key trends, benefits and obstacles in mutual relations. The fourth and last part of the paper summarizes what the goals of Serbian action towards the United Kingdom should be, and in what way certain strategic, but also more concrete political decisions of Serbia can affect bilateral relations between the two countries.
Keywords: United Kingdom; Great Britain; Brexit; Serbia; Strategy; Foreign Policy; Defence; Russia; China; NATO